The influence of ants on the environment and their relationship with ecosystem components - Mikhaleiko, Bogdan A.; Babenko, Andrei S.; Khovalyg, Aldynay O.; Mongush, Sayana D.; Maria I. Dongak; Kanzivaa, Svetlana O.; Ondar, Sergey O.; Kirpotin, Sergey N. (Altai State University, 2024)
Having a wide geographical distribution and, as an engineering species, actively transforming the landscapes they inhabit, ants have a significant impact on the environment, creating new biogenic landforms and changing a number of its parameters, including biotic ones. This review is devoted to the consideration of the diverse environment-forming activities of ants in different regions of the world. An analysis of the scientific literature carried out in this context revealed a clear disproportion between the fairly good knowledge of tropical regions and the insufficient knowledge of temperate latitudes. The environment-forming activity of ants actively populating grasslands removed from agricultural use: steppes, continental and floodplain meadows of temperate latitudes has been especially poorly studied, which determines the undoubted priority of this area of research.